E-Goverment: Meningkatkan Efisiensi dan Efektivitas Pelayanan Publik di Indonesia - Rizky, Andryan Muhammad; Pratiwi, Melita Putri; Chairunnisa, Alika; Aiko, Iftitah Azzahra; Ariesmansyah, Andre (Innovative: Journal Of Social Science Research, 2025)
This article discusses the implementation of E-Government in Indonesia as an effort to enhance the efficiency and effectiveness of public services through the digitalization of government processes. This study employs a literature review method to analyze policies, benefits, challenges, and case studies from regions like Denpasar and Pare-Pare that have successfully implemented E-Government. The findings indicate that E-Government can accelerate administrative processes, improve service transparency, and expand public access to information. However, its implementation faces challenges such as limited infrastructure in remote areas, a lack of human resources with technological expertise, and data security risks. To address these obstacles, strengthening telecommunication infrastructure, providing technology-based human resource training, integrating systems across institutions, and implementing stricter data security regulations are recommended. These measures aim to support an inclusive and sustainable digital transformation through E-Government.